Про розв’язність системи лінійних рівнянь над областю головних ідеалів - Прокiп, В.М. (Український математичний журнал, 2014)
Установлены необходимые и достаточные условия разрешимости системы линейных уравнений над областью главных идеалов. Предложен метод нахождения ее решений. We propose new necessary and sufficient conditions for the solvability of a system of linear equations over the domain of principal ideals and an algorithm for the solution of this stem.